2020
DOI: 10.1080/17435390.2020.1777475
|View full text |Cite
|
Sign up to set email alerts
|

The effects of genotype × phenotype interactions on silver nanoparticle toxicity in organotypic cultures of murine tracheal epithelial cells

Abstract: Silver nanoparticles (AgNP) are used in multiple applications but primarily in the manufacturing of antimicrobial products. Previous studies have identified AgNP toxicity in airway epithelial cells, but no in vitro studies to date have used organotypic cultures as a high-content in vitro model of the conducting airway to characterize the effects of interactions between host genetic and acquired factors, or gene × phenotype interactions (G×P), on AgNP toxicity. In the present study, we derived organotypic cultu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…Within the AEP framework, we integrated dosimetric data for intracellular uptake and/or localization of Ag mass associated in the lungs of different animal genotypes (Figure 3A). Interestingly, we observed relevant IVIVE from the Nicholas et al to the Scoville et al study, as the levels of intracellular uptake and/or localization of Ag mass associated in our organotypic cultures derived from A/J and C57BL6/J mice translated to a similar pattern of Ag mass associated in the lungs of A/J and C57BL6/J mice (Nicholas et al, 2020a; Scoville et al, 2017).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Within the AEP framework, we integrated dosimetric data for intracellular uptake and/or localization of Ag mass associated in the lungs of different animal genotypes (Figure 3A). Interestingly, we observed relevant IVIVE from the Nicholas et al to the Scoville et al study, as the levels of intracellular uptake and/or localization of Ag mass associated in our organotypic cultures derived from A/J and C57BL6/J mice translated to a similar pattern of Ag mass associated in the lungs of A/J and C57BL6/J mice (Nicholas et al, 2020a; Scoville et al, 2017).…”
Section: Resultssupporting
confidence: 54%
“…Similar levels of Ag mass associated in BEAS‐2B cells have been reported in other in vitro studies (Cronholm et al, 2013; Gliga et al, 2014; Jeannet et al, 2015; Kim et al, 2011, 2014; Nymark et al, 2013; Zhang et al, 2015). In our previous study of G × E effects on AgNP toxicity, we observed the highest levels of Ag mass associated in “AJ:T2‐Skewed” organotypic cultures when normalized by ICP‐MS (Nicholas et al, 2020a).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…We previously characterized the effects of interactions between host genetic and acquired factors, or gene  environment (G  E) interactions, on AgNP toxicity (Nicholas et al, 2019). Understanding G  E effects is important for identifying sensitive populations, whose underlying genetics or diseases could directly modify their response to AgNP exposures.…”
mentioning
confidence: 99%